2012
DOI: 10.1155/2012/325675
|View full text |Cite
|
Sign up to set email alerts
|

Primary Bilateral Non-Hodgkin's Lymphoma of the Adrenal Gland: A Case Report

Abstract: Primary bilateral non-Hodgkin's lymphoma (NHL) of the adrenal gland is a very rare entity. Indeed less than 60 cases have been reported in the literature. Hence, we report a case of high-grade lymphoma of both adrenal glands that was found in a young patient of 32 years of age. The patient was admitted in the emergency department of our hospital with a profile of hemorrhagic shock. After stabilization, the imaging investigations demonstrated large bilateral adrenal masses. The CT-scan guided biopsy of both adr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The aetiopathogenesis is unclear but may be related to previous autoimmune adrenalitis, Epstein–Barr virus and mutations p53 and c-Kit 3. As with our case report, primary adrenal lymphoma is common in elderly men (median age 68 years and 2–3:1 male:female ratio) 4. Treatment of adrenal lymphoma includes surgery, radiotherapy and chemotherapy.…”
Section: Discussionsupporting
confidence: 63%
“…The aetiopathogenesis is unclear but may be related to previous autoimmune adrenalitis, Epstein–Barr virus and mutations p53 and c-Kit 3. As with our case report, primary adrenal lymphoma is common in elderly men (median age 68 years and 2–3:1 male:female ratio) 4. Treatment of adrenal lymphoma includes surgery, radiotherapy and chemotherapy.…”
Section: Discussionsupporting
confidence: 63%
“…The recommended treatment regimen for PAL is R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone), a classical chemotherapy regimen (20), with chemotherapy being the typical treatment. It has been reported that surgery is not recommended for treatment (21). This disease appears to have a poor prognosis, and the median survival of patients with PAL is reported to be ~1 year (22).…”
Section: Discussionmentioning
confidence: 99%
“…Certain conditions associated with bilateral adrenal lesions with adrenal insufficiency are metastatic lung carcinoma, pheochromocytoma, tuberculosis and amyloidosis 6. PAL often presents with bilateral tumour masses (in 70% of cases) 7 8. Elderly men are most commonly affected by PAL; in particular, a prior study observed that PAL patients ranged between 39 and 89 years of age with a mean age of 68 years 8.…”
Section: Discussionmentioning
confidence: 99%
“…PAL often presents with bilateral tumour masses (in 70% of cases) 7 8. Elderly men are most commonly affected by PAL; in particular, a prior study observed that PAL patients ranged between 39 and 89 years of age with a mean age of 68 years 8. Primary adrenal non-Hodgkin's lymphoma is a rare extranodal involvement that accounts for <3% of PAL cases 9…”
Section: Discussionmentioning
confidence: 99%